Collaborative engagement versus collective estrangement: examining student retention in undergraduate mathematics using social ecology networks - Geoff Woolcott; Dan Chamberlain (Discover Education)
Abstract Mathematics is important in industrialized societies, but higher education is facing challenges in attracting students who will engage with and complete mathematics programs. Analytical methods are now available that can show the way forward by considering the numerous and diverse factors that influence student success in undergraduate mathematics. This article examines the use of an innovative combination of social network theory and social ecology theory, as social ecology networks, to examine the multiple factors that affect retention and attrition of undergraduate mathematics students. Results from a novel multifactorial analysis of case study data from an Australian regional university demonstrate the advantages of showing how students can be connected in proximal factor relationships within their undergraduate ecosystem, that is, directly to environmental factors in one-to-one relationships. The findings suggest that this type of student-centered and place-based analysis has much to offer in terms of encouraging collaborative engagement rather than the current collective estrangement that has resulted in reduced numbers of students attempting and completing mathematics programs in higher education.